Revista tipográfica (1888-1890): Professional identity and technical conditions in typographic workshops in rio de janeiro - de Luca, Tania Regina [UNESP] (EDIPUCRS, 2020)
The typographers, by the very nature of their activity, which presuppo-sed the mastery of reading, writing and of the process of production of printed matters, were among the most active professional in the launching of publications, whether as managers or collaborators. Their periodicals were designed to deal with specific issues of their occupation, but there were also those that extrapolated the problems related to the graphic workshops and discussed the conditions of workers in general. Thus, in different latitudes, these typographers were among the first ones to organize themselves into associations and to articulated their demands and criticize social order. In this article, we focus on Revista Tipográfica, which circulated in Rio de Janeiro between 1888 and 1890. We will analyse the publication from a historical perspective, when providing an overview of its orga-nizers, characteristics and trajectory. It is important to highlight the perception that the typographers had towards their profession, their own representation and the current standard of typographic art in Brazil. During the period that the magazine circulated, the more sophisticated publications, with regard to the physical quality such as A Ilustração (Paris, 1884-1892), had to be produced beyond national borders.
Revista tipográfica (1888-1890): identidad profesional y condiciones técnicas en los talleres tipográficos de rio de janeiro
Revista tipográfica (1888-1890): identidade profissional e condições técnicas nas oficinas tipográficas do rio de janeiro
Keywords: A Ilustração; Identity; Luiz da França e Silva; Revista Tipográfica; To be a typogra-pher